Role of co-solute in biomolecular stability: glucose, urea and the water structure - Xammar Oro, Juan R. de (2001)
We have studied the action of urea and glucose on the stability of DNA and micelles. We measured the melting temperature of aqueous solutions of DNA with urea or glucose as a cosolute; we have also measured the changes in the critical micelle concentrations (cmc) of Sodium Dodecyl Sulfate and Triton X-100 by addition of urea and glucose. Our experimental results show that glucose increases the melting temperature of DNA and decreases the cmc, while urea acts in the contrary direction. The effects of urea and glucose on the stability of DNA and micelles can be explained by the weakening and enhancement of hydrophobic interactions, respectively. These effects on hydrophobic interactions are discussed in this paper.